2018
DOI: 10.1136/bcr-2018-225644
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral cataracts as the presenting feature of type 1 diabetes in an 11-year-old girl

Abstract: Paediatric cataracts can present a diagnostic dilemma to ophthalmologists. Next-generation DNA sequencing (NGS) has been promoted as a tool to expedite the diagnosis of an underlying cause in such cases. The authors present an unusual case of bilateral cataracts in an 11-year-old girl as the first presenting feature of new type 1 diabetes mellitus. Prompt diagnosis and subsequent management of this potentially life-threatening condition were achieved through careful history taking and targeted biochemical test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Early cataract was described as a rare ocular complication in pediatric patients at diabetes onset by a series of case reports and single center studies 11–18 . Simunovic et al reviewed the literature and found 16 publications describing 74 pediatric patients with cataract.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early cataract was described as a rare ocular complication in pediatric patients at diabetes onset by a series of case reports and single center studies 11–18 . Simunovic et al reviewed the literature and found 16 publications describing 74 pediatric patients with cataract.…”
Section: Introductionmentioning
confidence: 99%
“…6 Early cataract was described as a rare ocular complication in pediatric patients at diabetes onset by a series of case reports and single center studies. [11][12][13][14][15][16][17][18] Simunovic et al reviewed the literature and found 16 publications describing 74 pediatric patients with cataract. These publications suggest that female gender, adolescent age, a long history of hyperglycemic symptoms, and a high HbA1c at diabetes diagnosis are risk factors for cataract development, while the rate of ketoacidosis at diabetes onset seems to be lower in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation